2016
DOI: 10.1002/admi.201600770
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Versatile Interconnection Layer by Solvent Treatment of PEDOT:PSS Interlayer for Air‐Processed Organic Tandem Solar Cells

Abstract: A robust and efficient interconnection layer (ICL) based on low conductive poly(3,4‐ethylenedioxythiophene)‐poly(styrenesulfonate) (PEDOT:PSS) and ZnO nanoparticles is implemented in a solution‐air‐processed, blade coated inverted polymer tandem solar cell. The commercial PEDOT:PSS (Heraeus Clevios P VP Al 4083) is modified with a fluorosurfactant to allow its deposition onto any hydrophobic active layer surface. However, this method alters the electrical and energetic properties of the PEDOT:PSS thus affectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Moreover, modifying PEDOT:PSS might affect unfavorably the distribution of the insulating PSS part, creating an energy barrier. Prosa et al proposed a simple approach to recover the good functioning of a PEDOT:PSS film deposited from a suspension including a surfactant (Zonyl FS‐300) . By simply rinsing the film with isopropanol, part of the surfactant and the excess of PSS at the surface of the layer could be removed.…”
Section: Tandem Solar Cellsmentioning
confidence: 99%
“…Moreover, modifying PEDOT:PSS might affect unfavorably the distribution of the insulating PSS part, creating an energy barrier. Prosa et al proposed a simple approach to recover the good functioning of a PEDOT:PSS film deposited from a suspension including a surfactant (Zonyl FS‐300) . By simply rinsing the film with isopropanol, part of the surfactant and the excess of PSS at the surface of the layer could be removed.…”
Section: Tandem Solar Cellsmentioning
confidence: 99%
“…In tandem OSCs, DPP-based polymers were always used in the top subcells to harvest low-energy photons. Quite a few research work was based on multithiophene and DPP blocks, such as poly[ (2,5- [73,74] [75][76][77][78] poly [3,6- [79] [80]…”
Section: Polymer Donorsmentioning
confidence: 99%
“…[33] To circumvent that, the pH neutral PEDOT:PSS analogues of m-PEDOT:PSS and highly conductive poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PH100) with high viscosity were used. [21,33,[38][39][40]58,70,[75][76][77]85,97,99,102,122,[127][128][129]132,138,144,164,208] Zhou and coworkers found that PEDOT:PSS with surfactant deposited on top of nonfullerene-based tandem OSCs might lead to chemical reaction between PEDOT:PSS and the NFA (IT-4F), which would be detrimental to the device performance. [100] To avoid the direct deposition of PEDOT:PSS on top of the active layer, they introduced a hydrogen molybdenum bronze (H x MoO 3 ) layer between the bottom active layer and PEDOT: PSS.…”
Section: The Icls For Tandem Oscsmentioning
confidence: 99%
“…Previously, in organic solar cells and perovskite solar cells, some polar solvents including ethylene glycol (EG), dimethyl sulfoxide (DMSO), dopamine, F4-TCNQ, dimethyl formamide (DMF), imidazole, etc. have been used as additives to enhance the PEDOT:PSS conductivity and tune the work-function [35][36][37][38]. Among them, DMSO exhibits superior advantages due to its good dielectric constant, dipolar moment, and relatively higher boiling point.…”
Section: Introductionmentioning
confidence: 99%